Control of CO2 vibrational dynamics via shaped-pulse coherent anti-Stokes Raman spectroscopy - Hendriks, Adriaan Jacobus (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017